Self-rated health and social classes in Slovenia: is there any relationship? - Farkas, Jerneja; Zaletel-Kragelj, Lijana (Anali PAZU, 2022)
Self-rated health is an established measure of health status and can be influenced by several social determinants. As countries remain culturally, politically, and economically distinct, previous findings on self-rated health and social class may not be directly applicable to Slovenian population. The aim of this study was to evaluate the relationship between self-rated health and social class in Slovenian adults. The study was based on the Countrywide Integrated Non-communicable Diseases Intervention (CINDI) Health Monitor database, which is updated approximately every 3 years by a cross-sectional survey. During 2008, 7,633/15,591 (49.0%) of posted self-administered questionnaires were retrieved. Prevalence per 100 population of poor self-rated health was determined. Logistic regression was used to determine unadjusted and adjusted (gender, age, marital status, educational level, kind of work, residence community, geographical region) estimates of association between poor self-rated health and social class. Question about self-rated health was answered by 7,302 participants and 701 (9.6%) reported to have poor self-rated health. A clear decrease in prevalence of poor self-rated health from 34.2% in lower to 3.1% in upper-middle/upper social class was observed. In an unadjusted model, the association between poor self-rated health and social class was significant across all social classes. After adjustment for potential confounders, the odds remained highest for those in the lower social class who rated their health as poor more than six times as frequently as those in upper-middle/upper social class (OR=6.10, 95% CI 3.34-11.16; p<0.001). Our study confirmed large differences in the prevalence of poor self-rated health across social classes. Participants from lower social class most frequently reported poor self-rated health. In the future, public health policy will have to address the incentives to reduce the social gradient in health.